Macroeconomic volatility and social vulnerability in Brazil : the Cardosa government (1995-2002) and perspectives - Macedo, Roberto (ECLAC SantiagoCL, 2003)
Addresses the social effects of macroeconomic volatility in Brazil, as well as the burdens and challenges it has been imposing on social policies.